Prevalence of old age hypertension and associated factors among older adults in rural Ethiopia - Shukuri A; Tewelde T; Shaweno T (Dove Medical Press, 2019)
Arif Shukuri,1 Tsegaye Tewelde,2 Tamrat Shaweno2 1Disease Prevention and Control, West Hararge Zonal Health Department, Harar, Ethiopia; 2Department of Epidemiology, Faculty of Public Health, Jimma University Institute of Health, Jimma, EthiopiaCorrespondence: Tamrat ShawenoJimma University Institute of Health, P.O. Box 378, Jimma, EthiopiaTel +251 91 249 3482Email babiynos@gmail.comBackground: Older adults are disproportionately affected by hypertension, which is an established risk factor for cardiovascular disease. Despite these facts, little information is available with regard to old age hypertension in Ethiopia. Thus, this study assessed old age hypertension and associated factors among older adults in rural Ethiopia.Methods: A community-based cross-sectional study design was employed among 418 selected permanent residents of Chiro town aged 50 years and older using simple random sampling technique. Data were collected face to face using a structured questionnaire which is adapted from the WHO Stepwise approach to surveillance of non communicable disease instrument, and was used to collect data on risk factors. Physical measurements were taken as per WHO STEP guidelines. The data were entered into Epi Data version 3.1 and exported to SPSS Version 20 for analysis. Bivariate and multivariable logistic regression analysis were conducted and statistical significance was declared at a p-value ≤0.05.Results: The overall prevalence of old age hypertension was 41.9% (95% CI: 37.2–46.6). Age ≥70 years (AOR: 1.91; 95% CI: 1.12–3.27), low intake of fruits (AOR: 2.45; 95% CI: 1.55–3.86), overweight/obese (AOR: 4.29; 95% CI: 2.48–7.42) and family history of hypertension (AOR: 2.95; 95% CI: 1.70–5.12) were significantly associated risk factors of hypertension.Conclusion: The prevalence of hypertension among older adults was high. Older age ≥70 years, low intake of fruits, overweight/obese and having a family history of hypertension were significantly associated with hypertension. Consideration should be given for community-based screening of hypertension among older adults. In addition, fruit consumption habits and maintaining normal weight should be encouraged.Keywords: old age hypertension, prevalence, Ethiopia